Performance appraisal system and performance appraisal model - Yulaf, Baybars (My University, 2003)
PERFORMANS DEĞERLENDIRME SISTEMI VE BIR PERFORMANS DEĞERLENDIRME MODELI Performans değerlendirme, çeşitli evrelerden geçerek günümüze kadar gelen, organizasyonların vazgeçemeyecekleri önemli bir yönetim aracıdır. Performans Değerlendirme felsefesi çok eskilere dayanmaktadır. Zaman içerisinde bir yönetim aracı olarak gelişen bu sistem, inişli-çıkışlı tarihinde çok yoğun eleştirilere maruz kalmış ve zaman zaman yöneticileri bu sistemi uygulayıp uygulamama konusunda tereddütte bırakmıştır. Son yıllarda Performans Değerlendirme sisteminde büyük değişiklikler olmuştur. Bir çok çalışma yapılmış, yeni uygulamalar başlatılmıştır. Bunların hepsinden amaç, sonuçta çalışanın ve organizasyonun performansını arttırmak olmuştur. Performans Değerlendirme, İnsan Kaynakları Yönetiminin bütün fonksiyonlarına veri sağlayan en önemli fonksiyondur. Her organizasyon kendi değerlendirme sistemini kurarken, bütün gelişmeleri dikkate almalı ve kendi yapısına en uygun olan değerlendirme sistemini seçmelidir. Kara Kuvvetleri de her organizasyon gibi mevcut değerlendirme sistemini ele almalı ve yeni gelişmeleri kendi Performans Değerlendirme Sistemine entegre etmelidir. Name and Surname: Baybars YULAF Field: Public Management Program: Human Resources Management and Development Supervisor: Professor Canan ÇETİN Degree Awarded and Date: Master - APRIL 2003 Performance Appraisal, Human Resources Management

PERFORMANCE APPRAISAL SYSTEM AND A PERFORMANCE APPRAISAL MODAL Performance appraisal is an important management tool, which has experienced so many stages so far. The philosophy of performance appraisal dates back to far past. This system day by day has been improved as a management tool and exposed to so many criticisms and sometimes administrators felt hesitation whether to use this system or not. Recent years there are big changes on the performance appraisal system and the main purpose of these changes is to improve organization and employees' performance. Performance appraisal is the most important function, which supplies data for Human Resources Management's all functions. Every organization, which decide to establish performance appraisal system, they should take into consideration all developments and choose the most suitable appraisal system for themselves. Like every organization The Land Forces should deal with its Performance Appraisal System and integrate the new developments into current appraisal system.
Keywords: Performans Değerleme; Personel Yönetimi